Long Term Follow up of Patients With Primary Obstetric Antiphospholipid Syndrome - Stanley Niznik; Micha J. Rapoport; Micha J. Rapoport; Orly Avnery; Aharon Lubetsky; Aharon Lubetsky; Ronen Shavit; Martin H. Ellis; Martin H. Ellis; Nancy Agmon-Levin; Nancy Agmon-Levin (Frontiers Media S.A., 2022)
Introduction: Primary obstetric antiphospholipid syndrome (OAPS) is defined by specific morbidities and/or losses of pregnancy in the presence of persistent antiphospholipid antibodies (aPL). This variant of APS is usually treated during pregnancy and the post-partum period. Data on occurrence of thrombotic event during long term follow-up of OAPS patients is limited.Methods: A multi-centre retrospectively cohort of female patients with primary APS (pAPS) was assembled during 2004-2019. Patients were grouped according to disease presentation as pure OAPS or thrombotic APS (tAPS) for those presenting with thrombosis. Clinical and serological data were compared between groups.Results: Of 219 pAPS female patients 67 (30.6%) were diagnosed with OAPS and 152 (69.4%) with tAPS. During >10 years of follow-up 24/67 (35.8%) OAPS and 71/152 (50%) tAPS suffered a new thrombotic event (p = 0.06), while obstetric morbidity was more likely in the OAPS group (31.3 vs. 10.5%, p < 0.001) respectively. Among patients with OAPS at presentation heart valve disease and the presence of ANA were related to thrombosis following diagnosis (25 vs. 4.7%, p = 0.02; and 45.8 vs. 20.8%, p = 0.04 respectively).Conclusion: Thrombotic event following diagnosis were common among female patients with pAPS regardless of disease presentation. Heart valve disease and ANA positivity may be risk factors for thrombosis during follow-up of patients presenting with pure OAPS.